Spowiednik i wyzwanie związane z pornografią - deLadurantaye, Paul (Teologia i Moralność, 2018)
Increasingly, many confessors are confronted with penitents who have become involved with pornography. This article provides some statistics illustrating the scope of pornography and then analyzes the harm that pornography causes, both to the dignity of the human person and in relation to the virtues of chastity and justice. The article invites confessors to help penitents understand that involvement with pornography is more than simply breaking a commandment, but rather affects a penitent’s capacity for self-giving and thus one’s authentic emotional and spiritual growth. Confessors should guide penitents who struggle with this issue to cultivate the true vision of human love in place of the distorted image offered by pornographic material. The confessor should be prepared to turn a penitent’s attention to effective spiritual remedies as well as in some cases suggesting a penitent seek professional assistance so that the authentic image of God may be restored and the penitent be helped to attain true freedom from the vice of pornography.